DIAGNOSING, EVALUATING AND MONITORING STUDENTS WITH SPECIAL NEEDS AND LEARNING DISABILITIES IN NORTH MACEDONIA - Usein, Arafat; Saban, Havva (International Scientific Journal Vision, 2024)
According to Macedonian educational legislation, from the school year 2022/23, all children with disabilities must be included in regular schools. However, throughout the world, children with disabilities and their families constantly experience a barrier in regard to theenjoyment of their basic human rights and to their inclusion in society. Aim of this paper is to put emphasize on inclusive education of all students with disabilities. So according to this legislation teachers should accept the inclusion of children with some types of disabilities in the regular classrooms. Their capacities are underestimated and their needs are given low priority. The barriers they face are more frequently a result of the environment in which they live rather than a result of their impairment. In literature, the current debate is no longer about what inclusion, special needs and learning disability is and why it is needed. The key question is how it is to be achieved. Moreover, in our country currently, the debate focuses on “full inclusive education”. Namely, according to the new Macedonian educational legislation, all children with disabilities must be included in regular schools. Children's rights are equal for all children and this right should be preserved. When the goal is full inclusion, it is essential for teachers to be competent and willing to work with children with disabilities. Therefore, the purpose of this paper is to explore the attitudes of teachers towards inclusive education of all students with disabilities, and also the factors they consider most important to the proper implementation of inclusive practices in regular schools.